2015
DOI: 10.19030/ajbe.v8i2.9131
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions Of Online Accounting Coursework

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…At the flagship and urban campuses, students had slightly higher GPAs in online classes. At the regional campuses, online GPAs were slightly lower than on-campus GPAs, which may support the results of studies on community college students that show lower pass rates for online students (Xu & Jaggars, 2011;Jaggars & Xu, 2010;Johnson et al, 2015;Shea & Bidjerano, 2017;Hart et al, 2018). While statistically significant, the differences found in this study could be considered practically insignificant, since the difference between the means of the online and on-campus GPAs was 0.10 or less at all three campus types.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…At the flagship and urban campuses, students had slightly higher GPAs in online classes. At the regional campuses, online GPAs were slightly lower than on-campus GPAs, which may support the results of studies on community college students that show lower pass rates for online students (Xu & Jaggars, 2011;Jaggars & Xu, 2010;Johnson et al, 2015;Shea & Bidjerano, 2017;Hart et al, 2018). While statistically significant, the differences found in this study could be considered practically insignificant, since the difference between the means of the online and on-campus GPAs was 0.10 or less at all three campus types.…”
Section: Discussionsupporting
confidence: 67%
“…Gutman (2012) describes concerns over online class quality as a barrier to faculty acceptance of online classes, stating that faculty are "skeptical about the effectiveness of courses delivered from a distance" and that many faculty still feel that online classes "are poor attempts to replace the teacher with technology" (p. 55). Taking this further, Grossman and Johnson (2015) found that business faculty were significantly less likely to accept transfer credit for classes taken in hybrid and online formats, despite equivalent grades and/or institution. Much of the faculty distrust of online education comes from the fact that online classes often have lower completion rates (Carr, 2000;Jaggars & Xu, 2010;Xu & Jaggars, 2011;Johnson et al, 2015;Shea & Bidjerano, 2017;Hart et al, 2018), even though a recent study conducted by Wisneski, Ozogul, and Bichelmeyer (2017) reported no significant differences in student performance when undergraduate students were allowed to take prerequisite and postrequisite courses in a variety of online and on-campus combinations in their required course sequences.…”
Section: Investigating the Impact Of Online Classes On Undergraduate mentioning
confidence: 97%
“…Studies have shown that positive attitudes of faculty toward technology have contributed to higher levels of computer skills, to the ability to teach online, the openness to accept university training, and feeling more freedom of personal expression (Broussard & Wilson, 2018;Glass 2017;Johnson, 2015;Pereira & Wahi, 2017). These studies suggested that faculty members with high levels of computer skills were more likely to teach online.…”
Section: Online Teaching At Hbcusmentioning
confidence: 99%
“…The literature shows both negative and positive attitudes toward online learning. Negative attitudes may have resulted from the lack of computer skills, workload, and university support (Chen, 2009;Grossman & Johnson, 2015;Glass, 2017;Mitchell & Geva-May, 2009;Pereira & Wahi, 2017).…”
Section: Faculty Attitudes Toward Online Education and Technologymentioning
confidence: 99%
“…Peng (2009, 263) properly noted that there seems to be a "hidden assumption" that the mere introduction of technology into the classroom somehow improves outcomes and that this "…assumption…receives little or no challenge from educators." Grossman and Johnson (2015) have demonstrated that faculty members tend to consider online courses less demanding of students and less proficient at instilling some skills than face-to-face courses. Yet, the emphasis placed on online course offerings continues.…”
Section: Introductionmentioning
confidence: 99%